The Religious Affairs Office's Role in Preventing Early Marriage in Kajang District, Bulukumba Regency, South Sulawesi - Syamsir Syamsir; Zainal Abidin (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2022)
The purpose of this research is to (1) determine the state of early marriage in the district. Kajang, Bulukumba-South Sulawesi, (2) The role of the District's Office of Religious Affairs (KUA) in preventing early marriage. South Sulawesi, Kajang, Bulukumba. This is a qualitative study in which the research process is continuous, so that the stages of data collection and data analysis occur concurrently during the research process. In this case, the collected data is processed and analyzed at the same time. The Office of Religious Affairs (KUA) in Kajang, Bulukumba, South Sulawesi, is the site of the research. The findings of the study show that: 1) Factors that cause early marriage, as for the reasons that cause early marriage, which is common in the Kajang Regency community. Bulukumba is a combination of a) economic factors, b) educational factors, c) parental factors, d) community mindset factors, e) pregnant out of marriage factors, and f) indigenous factors. The impact of early marriage, both positive and negative. 2) The role of KUA is to conduct socialization to prospective brides who want to get married in order to foster a good household, love each other, and prioritize deliberation if they encounter problems; the guidance is in the form of socialization or coming at the time of attending invitations, and the community is counseled. The marriage law regarding the age limit for marriage regarding the correct reproductive system and the dangers of working with local village youth leaders or village officials and other agencies are among the socialization materials.–Penelitian ini adalah bertujuan untuk mengetahui (1) Kondisi Pernikahan dini di Kec. Kajang, Kab. Bulukumba Sulawesi-Selatan, (2) Peran Kantor Urusan Agama (KUA) dalam mencegah pernikahan dini di Kec. Kajang, Kab. Bulukumba Sulawesi Selatan. Jenis Penelitian ini adalah penelitan kualitatif, dimana proses penelitian berkesinambungan sehingga tahap pengumpulan data dan analisis data yang dilakukan secara bersamaan selama proses penelitian. Dalam hal ini data yang dikumpulkan diolah dan dianalisis secara bersamaan. Lokasi penelitian di Kantor Urusan Agama (KUA) di Kec. Kajang, Kab. Bulukumba Sulawesi-Selatan. Adapun hasil penelitian yang dilakukan menunjukkan bahwa; 1) Faktor penyebab terjadi pernikahan dini, adapun alasan yang menyebabkan terjadinya pernikahan dini yang sering tejadi di lingkungan masyarakat Kajang Kab. Bulukumba yaitu a). Faktor Ekonomi, b). Faktor Pendidikan, c). Faktor orang Tua, d). Faktor Pola Fikir Masyarakat, e). Faktor Hamil di luar Nikah, dan f). Faktor Adat. Dampak dari pernikahan dini, diantaranya negatif dan positif. 2) Adapun peran KUA adalah melakukan sosialisasi kepada calon mempelai yang mau menikah untuk membina rumah tangga yang baik, saling menyayangi dan mengedepankan musyawarah jika mendapati masalah, bimbingan tersebut berupa sosialisasi atau datang pada saat menghadiri undangan dan memberikan penyuluhan kepada masyarakat. Materi sosialisasi antara lain Undang-Undang pernikahan mengenai batas usia nikah tentang sistem reproduksi yang benar serta bahaya dan bekerja sama dengan tokoh pemuda desa setempat atau perangkat desa maupun instansi lainnya.